(untitled) (Eurasian Journal of Ecology, 2024)
The aim of the study is to assess the impact of radiation pollution on the stability of the genome and human health, taking into account the long-term genetic consequences. Measurements of gamma activity showed that the radiation level of the surveyed territory of the landfill and adjacent settlements is in the range of 0.06-0.014 mSv/h. Of particular importance in this regard is the study of the mechanisms of individual sensitivity to radiation and the role of the DNA repair system [1,36]. Molecular genetic studies of the DNA of blood cells and cytogenetic analyses of people living in the zone of influence of the radioactive waste landfill revealed the spread of several mutant genotypes, which indicates the likelihood of an increased risk of environmental diseases in persons with pronounced genome instability. The radiation level on the territory of the landfill and adjacent settlements is in the range of 0.06-0.014 mSv/h. By genotyping the XRCC1 Arg399Gln DNA repair gene, it was found: homozygous Arg/Arg (89+159), heterozygous Arg/Gln (248+159+89 ), homozygous Gln/Gln (248). The genotype distribution is as follows: XRCC1 Arg/Arg - 15 people, XRCC1 Arg/Gln - 14 people, XRCC1 Gln/Gln - 1 person. Key words: mutagens, radiation, environment, genes, hereditary diseases, genome